1998
DOI: 10.2165/00019053-199813010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Economic Aspects of Antibacterial Adverse Effects

Abstract: The economic impact of adverse effects is often understated. Increased hospitalisations attributed to adverse drug reactions alone account for billions of dollars each year within the US healthcare system. Although most classes of antibacterials are well tolerated, severe reactions do occur and can add significantly to the cost of care. Among hospitalised patients, antibacterial adverse effects account for nearly 25% of adverse drug reactions. Published pharmacoeconomic data on direct and indirect costs of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…In a few countries, antibiotic prescribing was higher such as in Kenya (73.4%) (Holloway and Henry 2014), Timor-Leste (70%) (Stanley Chindove and Martins 2012), and Sudan (70.4%) (Holloway and Henry 2014). Unnecessary prescribing of antibiotics is a worldwide problem that eventually leads to ADRs and frequent hospital admissions (Beringer et al 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few countries, antibiotic prescribing was higher such as in Kenya (73.4%) (Holloway and Henry 2014), Timor-Leste (70%) (Stanley Chindove and Martins 2012), and Sudan (70.4%) (Holloway and Henry 2014). Unnecessary prescribing of antibiotics is a worldwide problem that eventually leads to ADRs and frequent hospital admissions (Beringer et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…According to another estimate, 20–50% of antimicrobial utilization is inappropriate (Čižman 2003) and this has a significant effect on the quality of health services provided (Shao-Kang et al 1998), treatment expenses (Segade 2000) and frequency of adverse drug reactions (ADRs). It has also been estimated that around one quarter (25%) of total ADRs can be attributed to antimicrobial use (Beringer et al 1998). Despite these concerns, the most alarming problem associated with irrational prescribing of antimicrobials is the development of resistance (Dellit et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among hospitalized patients, antibacterials account for nearly 25% of drug-related adverse events [8]. Many adverse effects are common to a particular drug class, whereas some are limited to a particular agent.…”
mentioning
confidence: 99%
“…Adverse effects of antibiotics are variable and can include phlebitis, hypersensitivity reactions, direct effects on tissues and organ systems, changes in microbial flora, and adverse interactions with other drugs [9]. Many of these adverse effects are not life-threatening but can have important economic implications by increasing the number of therapeutic interventions needed and the duration of the hospital stay [8]. To minimize the potential for serious adverse effects, clinicians should know the which adverse effects are associated with the antibiotics selected for their patients.…”
mentioning
confidence: 99%
“…4 This overuse of antibiotics has several downsides, including development of bacterial resistance, 5 side effects, 4,6 and costs. 6 Similarly, there is little conclusive evidence for benefits from symptomatic treatments, [7][8][9] which are often used inappropriately 10 and can cause side effects. 7,8 A systematic review on the effectiveness of OTC medications for acute cough found no benefit from codeine or antihistamines.…”
Section: Introductionmentioning
confidence: 99%